Cholesterol Protects Against Acute Stress-Induced T-Tubule Remodeling in Mouse Ventricular Myocytes - Nikouee, Azadeh; Uchida, Keita; Moench, Ian; Lopatin, Anatoli N. (Frontiers in Physiology, 2018)
Efficient excitation-contraction coupling in ventricular myocytes depends critically on the presence of the t-tubular network. It has been recently demonstrated that cholesterol, a major component of the lipid bilayer, plays an important role in long-term maintenance of the integrity of t-tubular system although mechanistic understanding of underlying processes is essentially lacking. Accordingly, in this study we investigated the contribution of membrane cholesterol to t tubule remodeling in response to acute hyposmotic stress. Experiments were performed using isolated left ventricular cardiomyocytes from adult mice. Depletion and restoration of membrane cholesterol was achieved by applying methyl-β-cyclodextrin (MβCD) and water soluble cholesterol (WSC), respectively, and t-tubule remodeling in response to acute hyposmotic stress was assessed using fluorescent dextran trapping assay and by measuring t-tubule dependent IK1 tail current (IK1, tail). The amount of dextran trapped in t-tubules sealed in response to stress was significantly increased when compared to control cells, and reintroduction of cholesterol to cells treated with MβCD restored the amount of trapped dextran to control values. Alternatively, application of WSC to normal cells significantly reduced the amount of trapped dextran further suggesting the protective effect of cholesterol. Importantly, modulation of membrane cholesterol (without osmotic stress) led to significant changes in various parameters of IK1, tail strongly suggesting significant but essentially hidden remodeling of t-tubules prior to osmotic stress. Results of this study demonstrate that modulation of the level of membrane cholesterol has significant effects on the susceptibility of cardiac t-tubules to acute hyposmotic stress.